Irreführende Geisterdebatte oder funktionale Notwendigkeit? Regimetheoretische Überlegungen zur Re- Regulierungsdiskussion am Beispiel der Weltumweltordnung - Jakobeit, Cord (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2000)
The paper starts with a presentation and critique of regime theoretical approaches to the understanding of world economic developments after 1945. Within the debate on re-regulation, the normative-idealistic calls for a global environmental organisation seem to ignore what we have learned so far about the change and the effectiveness of international regimes. A fundamental regime change requires the consensus of the hegemon and/or the hegemonial group. And regime effectiveness does not primarily depend upon hierarchical organisational structures. Rather than advocating a global environmental organisation, from an ecological perspective the reform-minded transnational discourse networks would be better adviced to work for the acceptance of ecologically oriented indicators for economic development within all existing organisations of the world economy.